Online Assignment Approach in Mechatronics System Design Course Using Google Classroom - S., Julius Fusis (Journal of Engineering Education Transformations, 2021)
In this cyber-driven world, assignments are submitted by higher education students by using pen, paper and pencil. With the outbreak COVID-19, the smart phones, tablets and computers/laptops play a vital role in educating the school students as well as higher education students. Despite the fact that the current generation students’ skill development is through additional education modes like assignments, formative assessment, and model-based assignments and so on, the teaching and learning process remains old. Very few educators are using smart education tools to collect feedbacks, to assess student’s knowledge using open CV’s like Padlet, Plickers, Moodle and Google classroom. The introduction of online assignment submission enriches the student’s skills, knowledge and content development skills. In this paper, the student’s activities for submission of assignment and subject content clarification are performed using Google classroom as an interactive tool. The introduction of online assignment submission creates measurable difference in student’s performance over traditional assignment submission. Although the student’s performance, student characteristics and study behavior are explained using case study on Mechatronics system Design course and its impact on the students for further improvement in education system.